PERBEDAAN INTENSITAS NYERI HAID SEBELUM DAN SETELAH TERAPI AKUPRESUR TITIK Li 4 DAN Ht 7 PADA REMAJA PUTRI - Sriani, Ni Luh; Suindri, Ni Nyoman; Utarini, Gusti Ayu Eka (Maternity and Neonatal : Jurnal Kebidanan, 2025)
Menstrual pain or dysmenorrhea is known as cramping pain in the lower abdomen during menstruation that some women experience. Providing acupressure therapy can reduce menstrual pain. This study aims to determine the difference in the intensity of menstrual pain before and after acupressure therapy at the Li 4 and Ht 7 points in adolescent girls at SMP N 3 Abang, Karangasem district. The method used in this research is pre-experimental using one group pre- test and post-test design. The research sample was 34 junior high school students who experienced menstrual pain. Data was collected using the Numeral Rating Scale (NRS). The data was then analyzed using the Wilcoxon test and the results showed that there were differences in the intensity of menstrual pain before and after acupressure therapy was given. Testing the difference between the pre-test and post-test obtained p-value = 0.000 (< 0.05), so it can be concluded that there is a difference in the intensity of menstrual pain before and after the intervention is given.